Responsible leadership lessons from the front line of sustainability and ethics - Moody-Stuart, Mark. (Sheffield Greenleaf Publishing, 2014)
As Chairman of the Royal Dutch Shell Group from 1991?2001 and of Anglo American plc from 2002?2009, Sir Mark Moody-Stuart is as qualified as anyone on the planet to discuss the realities, dilemmas and lessons to be learned from the last 20 years of corporate engagement with sustainability, ethics and responsibility. In this unique book ? part memoir, part confessional, part manifesto for leadership ? we hear a unique voice from the front line of corporate responsibility. Moody-Stuart retraces the steps of a remarkable journey from being a postgraduate geologist to being at the helm of two of the largest corporations in the world.
Includes bibliographical references and index.
Keywords: Moody-Stuart, Mark, 1940-